3D printing of dual phase-strengthened microlattices for lightweight micro aerial vehicles. (August 2021) - Xiao, Ran; Li, Xiang; Jia, Huaiyuan; Surjadi, James Utama; Li, Jingqi; Lin, Weitong; Gao, Libo; Chirarattananon, Pakpong; Lu, Yang
Graphical abstract: Highlights: Dual-phase strengthening mechanism-inspired microlattice metamaterial was designed. The metamaterial's strength, stiffness and energy absorption ability were enhanced. Large-scale metamaterial was 3D printed and applied to a micro aerial vehicle (MAV). The MAV shows greatly increased flight duration with considerable weight reduction. Abstract: The rapid advancement in CAD and 3D printing technology have brought the rise of mechanical metamaterials which inspired from nature and have optimized microstructural features to exhibit superior mechanical properties over conventional materials for various structural applications. Here, by adopting dual-phase strengthening mechanism in crystallography, we proposed a microlattice strengthening strategy which incorporates stretching-dominated octet-truss (OCT) units as the second phase particles into the diagonal planes of the bending-dominated body-centered cubic (BCC) lattice matrix, to form an anisotropic OCT-BCC lattice. The OCT-BCC dual-phase microlattice possess superior specific compressive strengths that are ~300% and 600% higher than BCC microlattices along its horizontal direction and longitudinal direction, respectively, accompanied with a significant increase in stiffness and energy absorption as well. Moreover, a large-scale OCT-BCC lattice metamaterial with dimensions up to 5.0 cm × 2.0 cm × 1.0 cm was successfully manufactured and integrated into a micro aerial vehicle (MAV). The metamaterial-integrated MAV has an airframe that is ~65% lighter than its bulk counterpart, resulting in a significant increase (~40%) in flight duration. This work not only provides an effective metamaterial enhancement design strategy, but also promotes the practical application of large-scale 3D printed metamaterial in the field of micro unmanned aerial vehicle.